Determining an author's impact with f-, c- and mh-indices. (12th April 2022) - Yadav, Manoj Kumar; Basyal, Devid Kumar; Paudel, Uttam
The existing indices like h-index, i10-index, g-index and author impact factor (AIF) do not take into account of the order of an author in the list of authors in an article. In this article we have proposed f-index to show the number of articles with the concerned author as the first author, c-index to show the number of articles with the concerned author as the corresponding author and mh-index as the modified form of h-index. The modified h-index mh incorporates only 50% credit of articles in which the concerned author is not the first author.